Perbandingan Mekanisme Penyelesaian Sengketa Tanah antara Hukum Adat dan Hukum Positif - Siti Nur Wahida; Zulfikar Putra; Farid Wajdi (JURNAL USM LAW REVIEW, 2026)
This study aims to analyze the mechanisms of land dispute resolution through the customary law of the Tolaki tribe and statutory law, as well as to compare the effectiveness of both in terms of legal certainty, costs, and the duration of the resolution process. The background of this study is based on the high potential for land disputes, which often lead to prolonged social conflicts, as well as the public’s confusion in choosing the appropriate resolution pathway. The research design employed is empirical legal research, where primary data was collected through interviews and observations, while secondary data was obtained from literature reviews using a descriptive-qualitative approach. Data analysis utilized the Miles and Huberman model, along with triangulation of sources and methods. The research findings indicate that the Tolaki tribe’s customary law, through deliberation symbolized by Kalosara, is more effective in terms of cost and time and maintains social harmony, whereas positive law provides formal legal certainty and strong enforceability but requires greater costs and time. It is concluded that both systems are complementary within the framework of legal pluralism. The novelty of this study lies in its empirical comparative analysis, which specifically compares the effectiveness of the two systems within a single framework of measurable indicators.  Penelitian ini bertujuan untuk menganalisis mekanisme penyelesaian sengketa tanah melalui hukum adat suku Tolaki dan hukum positif serta membandingkan efektivitas keduanya ditinjau dari aspek kepastian hukum, biaya, dan lama waktu penyelesaian. Latar belakang penelitian ini didasarkan pada tingginya potensi sengketa pertanahan yang sering menimbulkan konflik sosial berkepanjangan serta kebingungan masyarakat dalam memilih jalur penyelesaian yang tepat. Jenis penelitian yang digunakan adalah penelitian hukum empiris, di mana data primer diambil melalui wawancara dan observasi, sedangkan data sekunder diambil dari studi kepustakaan dengan pendekatan deskriptif-kualitatif dan metode analisis data menggunakan model Miles dan Huberman serta triangulasi sumber dan metode. Hasil penelitian menunjukkan bahwa hukum adat suku Tolaki melalui musyawarah dengan simbol Kalosara lebih efektif dari segi biaya dan waktu serta menjaga keharmonisan sosial, sedangkan hukum positif memberikan kepastian hukum formal dan kekuatan eksekutorial yang tegas namun memerlukan biaya dan waktu lebih besar. Disimpulkan bahwa kedua sistem bersifat saling melengkapi dalam kerangka pluralisme hukum. Kebaruan penelitian ini terletak pada kajian komparatif empiris yang secara spesifik membandingkan efektivitas kedua sistem dalam satu kerangka indikator yang terukur.
Keywords: Hukum Adat; Hukum Positif; Sengketa Tanah